2015
DOI: 10.4103/1119-3077.154216
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Demirjian method for dental age estimation for Southern Turkish children

Abstract: It is appropriate to use the Demirjian method in southern Turkish children; however, a revision is needed in some age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
2
8
0
2
Order By: Relevance
“…Results of the present study agree with a previous one, the mean ages at A, C, D, E, F1, G, G1 developmental stage were lower for males than for females and B and F were lower for females than males ( Table 2). This result is confirmed by Zhai, Gungor, Solari, Mincer et al [8,13,16,20] Compared with the present study and similar results are seen in the mean ages of the third molar at given stages of tooth development. However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results of the present study agree with a previous one, the mean ages at A, C, D, E, F1, G, G1 developmental stage were lower for males than for females and B and F were lower for females than males ( Table 2). This result is confirmed by Zhai, Gungor, Solari, Mincer et al [8,13,16,20] Compared with the present study and similar results are seen in the mean ages of the third molar at given stages of tooth development. However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults.…”
Section: Discussionsupporting
confidence: 81%
“…However, it is observed at all groups that crown-root formation earlier completed in the Turkish children and young adults. In previous studies conducted in Turkish populations, it has been reported that dentition shows gender differentiation, with that in females preceding that in males [13][14][15]17,19,21]. Karadayi et al [19] described that this difference was usually in only one stage and not in all teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2] The calcification of a tooth is divided into eight stages, and each stage has been designated a particular score which is different for boys and girls. [2] Although numerous studies have been done utilizing this method in different ethnic populations,[6789] the most commonly witnessed drawback is that the method is time consuming[2] and less user friendly as numerous tables have to be referred to. Thus, the authors felt the need to simplify this tedious process and prepare a comprehensive chart compiling data from all the original tables of Demirjian (DAEcc) and test its interpretation and ease of applicability by undergraduate BDS students.…”
Section: Introductionmentioning
confidence: 99%